Digital Technology Transformation in Enhancing Public Participation in Democratic Processes - Suherlan, Suherlan (Technology and Society Perspectives (TACIT), 2023)
In the era of globalisation and the development of digital technology, the role of technology in various aspects of life is increasing. One of the areas significantly affected is the democratic process in society. This research aims to analyse the transformation of digital technology in increasing people's participation in the democratic process. The current research type is qualitative. Data collection techniques include listening and recording important information to conduct data analysis through data reduction, data display, and conclusion drawing. The results showed that the transformation of digital technology has brought a significant impact on public participation in the democratic process. The availability of online platforms, easy access to information, and the ability to interact with political leaders have changed the way individuals engage in political decision-making. Despite the positive potential, there are challenges and risks that need to be addressed in order for public participation in the digital era to truly contribute to the strengthening of democratic principles.